Dual‐Sites Coordination Engineering of Single Atom Catalysts for Flexible Metal–Air Batteries. Issue 30 (19th June 2021) - Yu, Deshuang; Ma, Yanchen; Hu, Feng; Lin, Chia‐Ching; Li, Linlin; Chen, Han‐Yi; Han, Xiaopeng; Peng, Shengjie
Abstract: Dual‐sites single atom catalysts hold promise for efficiently regulating multiple reaction processes and explicitly explaining the underlying mechanisms. However, delicate atomic engineering for dual‐site single atom catalysts remains a huge challenge. Herein, atomically dispersed Fe‐Ni single atoms embedded in a nitrogen‐doped carbon matrix (FeNi SAs/NC) are successfully developed with extraordinary activity for electrocatalytic oxygen reduction and evolution reactions (ORR/OER). The atomic FeNi SAs/NC catalyst displays high onset potential (0.98 V) and half‐wave potential (0.84 V) for the ORR, as well as, low overpotential of (270 mV) at 10 mA cm −2 for the OER. The density functional theory calculations indicate that the Fe site as the active center can facilitate the four‐electron reaction process, while Ni sites regulate the electronic structure of Fe sites and further reduce the energy barrier of the rate‐determining step. In addition, the nitrogen‐doped carbon matrix prevents the metal atoms from aggregation and corrosion, leading to the improvement of catalyst durability. As a proof of concept, flexible quasi‐solid‐state zinc– and aluminum–air batteries assembled with the FeNi SAs/NC catalyst exhibit superior peak power densities and discharging specific capacities outperforming the commercial Pt/C. This work provides rational guidance for the synthesis of bifunctional electrocatalysts in next‐generation energy devices for flexible consumer electronics. Abstract : Unique noble metal‐free electrocatalysts with atomically dispersed Fe‐Ni dual‐sites are precisely designed and present superior oxygen reduction and evolution reaction reactivity under alkaline conditions, which provides a perspective and guidance for the design of efficient catalysts for metal–air batteries.